A just defiance : bombmakers, insurgents, and the treason trial of the Delmas Four - Harris, Peter, 1956- (University of California Press, 2012)
Both a riveting courtroom drama and a real-life thriller, A Just Defiance tells the story of four young black South Africans who were arrested for a string of political murders in 1987. In gripping prose, Peter Harris--the white lawyer who defended the men--describes how he came to understand, while constructing the case to save the defendants from the death penalty, the chain of events that led them to undergo training at ANC camps in Angola and return to their homeland to execute some of the apartheid regime's most notorious collaborators.